GGE biplot analysis of Dioscorea rotundata cultivar tela genotypes in Ghana - Otoo, E.; Asiedu, Robert (2009)
A five-year study involving 38 genotypes of D. rotundata cultivar Tela was evaluated in 15 environments from 2000 to 2004 using CRD. The three locations were Bodwease (Coastal Savanna), Fumesua (Forest) and Wenchi (Forest-Savanna Transition). The objective was to assess the effect of genotype and genotype x environment interaction on the tuber yield of 38 white yam (D. rotundata L. cv. Tela) genotypes via GGE (genotype plus genotype x environment) biplot methodology. Significant differences (p<0.005) were observed among the genotypes with respect to genotype, environment and genotype by environment interactions. Biplot analysis identified three mega-environments corresponding to three agroecologies. Fumesua environments were most representative and discriminating. Bodwease environments except BOD04 were most discriminating but most non-representative and Wenchi least discriminating and least representative. Three winning genotypes, G10, G18 and G1, were the winning genotypes in Bodwease, Fumesua and Wenchi respectively, with G18 as the most stable and high yielding D. rotundata cv. Tela genotype.